Bishop Policarp Morușca in service of the church in Bassarabia (Confluenţe Bibliologice, 2024)
The article is dedicated to Bishop Policarp Morușca, whose life was devoted to the service of the Church in Bassarabia, with significant contributions to the restoration and spiritual revitalization of this region. Born in 1883 into a priestly family, he worked as a teacher, parish priest, military confessor, and later as a bishop. After being tonsured into monasticism and becoming a bishop, he shepherded in America and later in Southern Bassarabia. Bishop Policarp Morușca was a prominent figure in the history of the Romanian Orthodox Church in Bassarabia during the first half of the 20th century. He uffering, the sick, and the needy, showing compassion and true Christian spirit. Bishop Policarp was a spiritual leader and a promoter of Romanian unity during a difficult period for Bassarabia. made a significant impact in promoting Christian and Romanian values in the region, during a time marked by turbulent political and social changes.
Keywords: Policarp Morușca (1883-1958); Romanian Orthodox Church